Spectrophotometric assays for measuring redox biomarkers in blood and tissues: the NADPH network - Aristidis S. Veskoukis; Nikos V. Margaritelis; Antonios Kyparos; Vassilis Paschalis; Michalis G. Nikolaidis (Taylor & Francis Group, 2018)
Nicotinamide adenine dinucleotide (NAD+/NADH) along with its phosphorylated form (NADP+/NADPH) are two molecules ubiquitously present in all organisms, and they play key roles as cofactors in fundamental catabolic and anabolic processes, respectively. The oxidation of NADPH to NADP+ initiates a cascade of reactions, where a network of molecules is implicated. The molecules of this cascade form a network with eminent translational potential in redox metabolism. A special point of interest is that spectrophotometric assays have been developed both for NADH/NADPH and the molecules directly regulated by them. Therefore, crucial molecules of the NADPH-dependent redox network can be measured, and the results can be used to assess the bioenergetic and/or oxidative stress status. The main aim of this review is to collectively present the NADPH-related molecules, namely NADPH, NADH, NAD+ kinase, NADPH oxidase, peroxiredoxin, thioredoxin, thioredoxin reductase, and nitric oxide synthase, that can be measured in blood and tissues with the use of a spectrophotometer, which is probably the most simple, inexpensive and widely used tool in biochemistry. We are providing the researchers with reliable and valid spectrophotometric assays for the measurement of the most important biomarkers of the NADPH network in blood and other tissues, thus allowing the opportunity to follow the redox changes in response to a stimulus.